2022
DOI: 10.1186/s13567-022-01049-6
|View full text |Cite
|
Sign up to set email alerts
|

YqeH contributes to avian pathogenic Escherichia coli pathogenicity by regulating motility, biofilm formation, and virulence

Lei Yin,
Baoyan Cheng,
Jian Tu
et al.

Abstract: Avian pathogenic Escherichia coli (APEC) is a pathotype of extraintestinal pathogenic E. coli and one of the most serious infectious diseases of poultry. It not only causes great economic losses to the poultry industry, but also poses a serious threat to public health worldwide. Here, we examined the role of YqeH, a transcriptional regulator located at E. coli type III secretion system 2 (ETT2), in APEC pathogenesis. To investigate the effects of YqeH on APEC phenotype and virulence, we constructed a yqeH dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The E. coli strains utilized for this study were AE81 and the AE81 mutant strain with yqeH deletion (Δ yqeH ) [ 9 ], ygeG deletion (Δ ygeG ) [ 12 ], and ETT2 cluster deletion (ΔETT2) [ 13 ], all constructed and stored by the Anhui Province Key Laboratory of Veterinary Pathobiology and Disease Control (Table 1 ). The espE3 gene deletion strain (Δ espE3 ) and complementary strain (C espE3 ) in AE81 were constructed in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The E. coli strains utilized for this study were AE81 and the AE81 mutant strain with yqeH deletion (Δ yqeH ) [ 9 ], ygeG deletion (Δ ygeG ) [ 12 ], and ETT2 cluster deletion (ΔETT2) [ 13 ], all constructed and stored by the Anhui Province Key Laboratory of Veterinary Pathobiology and Disease Control (Table 1 ). The espE3 gene deletion strain (Δ espE3 ) and complementary strain (C espE3 ) in AE81 were constructed in this study.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used ygeG [ 12 ] and yqeH [ 9 ] coded in the ETT2 cluster, which was shown to affect the virulence of APEC in our previous studies, as a representative to test whether the ETT2 genes affect the transcription of espE3 . The effects of ETT2, ygeG and yqeH on the transcription level of the espE3 gene were detected by fluorescence quantitative PCR as described previously [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the degenerative form of ETT2 may contribute to reducing the virulence and serum survival activity in bacteria ( Wang et al, 2016a ). Multiple components of ETT2 are involved in the pathogenicity of APEC ( Wang et al, 2016a ; Fu et al, 2021 ; Tu et al, 2021 ; Li et al, 2022 ; Xue et al, 2022 ; Yin et al, 2022 ). Our research shows that the transcriptional regulator DctR can regulate the expression of ETT2 and affect the virulence and pathogenicity of APEC ( Zhang et al, 2021 ).…”
Section: Pathogenic Mechanism and Virulence Factors Of Avian Pathogen...mentioning
confidence: 99%